Solving MHD Hybrid Nanofluid Flow Over a Shrinking Sheet with Quadratic Velocity using Shooting Technique - NAZRI, NURAIN IZZATI; AMAN, FAZLINA (Enhanced Knowledge in Sciences and Technology, 2024)
This research presents analysis on solving magnetohydrodynamics (MHD) hybrid nanofluid flow over a stretching/shrinking sheet with quadratic velocity using shooting technique. A similarity transformation is used to convert the governing equation from partial differential equations to ordinary differential equations using a set of similarity variables, and then the solutions are obtained using the shooting technique with RKF45 method in Maple software. The outcome indicates that an increment of alumina nanoparticles and magnetic parameters increase the skin friction coefficient. Further, this study confirmed the subsistence of non-uniqueness solutions in the hybrid Al2O3-Cu/H2O nanofluid for a particular range of the shrinking parameter, while a unique solution appears in the stretching case.